Достоевский в игровом мире Б. Акунина - СНИГИРЕВА, ТАТЬЯНА АЛЕКСАНДРОВНА; ПОДЧИНЕНОВ, АЛЕКСЕЙ ВАСИЛЬЕВИЧ (SlavVaria, 2021)
Dostoevsky in the Game World of B. Akunin. The article identifies two types of inclusion of Dostoevsky’s legacy in the artistic world of B. Akunin: an open declaration of the work based on which the text is created, and intertextual game with Dostoevsky’s work as a whole. The research material was “A Provincial Detective, or The Adventures of Sister Pelagia” and the novel “F. M.” It is shown that B. Akunin in the trilogy about the Russian provinces directly names the sources (mainly Dostoevsky’s “great Pentateuch”), which removes intertextuality, since it manifests itself during the decoding operation. Study of the genre specificity of the novel “F. M.” leads to the conclusion about the existence of a metatext layer in the text, indicates an increased author’s self-irony and self-reflection, which is a sign of readiness to supplement the detective-adventurous direction of creativity with other artistic strategies.